A cross-sectional study of etiological and sensitivity profiling of meningitis in under-five children - Tanushree Gahlot; Dimple Kasana (International Journal of Mycobacteriology, 2021)
Objectives: The study aimed to understand the organism spectrum and antibiotic sensitivity profile of acute bacterial meningitis in pediatric population. Methods: A cross-sectional study was conducted at the department of microbiology of a tertiary care center for a period of 18 months. Suspected cases of meningitis between 1 and 60 months of age were considered for the study. All cases underwent cerebrospinal fluid tap for direct microscopy (DM), Gram staining, and culture sensitivity. Results: The mean age of the study patients was 10.42 months, with 61.7% of males and 38.3% of females. DM and culture were positive in 22.90% and 28.00% of the patients, respectively. On Gram stain, there were 29 (59.18%) cases of Gram positivity and 20 (40.82%) cases of Gram negativity. The culture growth showed that Acinetobacter spp. was isolated in 15 (30.6%) of the cases. Enterococcus spp. was isolated in 9 (18.4%) of the cases. Klebsiella pneumoniae was isolated in 8 (16.3%) of the cases. Staphylococcus aureus was isolated in 8 (16.3%) of the cases. Enterobacter spp. was isolated in 3 (6.12%) of the cases. Pseudomonas aeruginosa was isolated in 3 (6.12%) of the cases. Streptococcus pneumoniae was isolated in 3 (6.1%) of the cases. The antibiogram of different agents showed wide variation, with colistin being 100% sensitive for Acinetobacter, Enterobacter, K. pneumoniae, and P. aeruginosa. Conclusion: The present study revealed that Acinetobacter, Enterococcus, K. pneumoniae, and S. aureus were the most common bacterial etiologic agents of ABM. The 100% antibiotic sensitivity of the organisms to some antibiotics may suggest the use of such antibiotics while awaiting for culture sensitivity reports.